Ayurvedic Perspective of Diabetic Peripheral Neuropathy - Nawfya. M.A; K. K. Remani (International Journal of Ayurveda and Pharma Research, 2021)
Diabetic Peripheral Neuropathies (DPN) are chronic debilitating complications following Diabetes mellitus. DPN refers to signs and symptoms of peripheral nerve dysfunction in a patient with Diabetes mellitus (DM) whom other causes of neuropathies have been excluded. The incidence of neuropathy is strongly associated with microvascular comorbidities. In Ayurveda, Prameha is one of Ashtamahagada, which will finally transform into Madhumeha without proper management. As there is no direct reference for diagnosing DPN in Ayurveda, it is essential to understand the causation and association of symptoms based on Tridoshas in Pradhana Vyadhi (main disease) as well as in Upadrava (complications). After analyzing both Madhumeha and DPN many similarities were found in respect of Nidana (etiology), Samprapti (pathology), and Lakshana (symptoms). Continuing Nidana even after Prameha Samprapti leads to its Upadrava. The features such as Kara pada daha (burning sensation of hand and foot), Pipeelika sancharamiva (tingling sensation), Swapa/ Supthi (numbness), Sosha (wasting), Angasada (weakness) are seen in Prameha either in the prodromal stage or in actual exhibition stage or complication stage can be correlated as DPN. The prevalence of DPN is also strongly associated with the duration of diabetes and glycemic control. Features of Avaranajanya and Dhatukshaya Madhumeha is to be differentiated and correctly diagnosed for the proper selection of treatment. Hence an attempt is made to review the differential diagnosis based on factors like etiopathology and symptoms of DPN in Ayurveda.